Efeito do fluoreto de sódio sobre a qualidade óssea das vértebras lombares de ratas ovariectomizadas - Villar, Lidiângela Dias (2004)
Osteoporosis is characterised by a reduced bone mass, followed by microstructural changes in the bone tissue, which increase the susceptibility to bone fractures. This pathology is most commonly found in women after menopause, being responsible for severe social and economic consequences. The use of fluoride has demonstrated the possibility to increase bone mass, especially of the axial skeleton. However, its effects on the bone quality are still controversial. The aim of this work was to investigate the effects of fluoride, as sodium fluoride (NaF), on bone tissue of ovariectomized rats (Ovx), which were used as an experimental model for osteoporosis, through the analysis of biomechanical, physical and biochemical parameters of the lumbar vertebrae. Wistar female rats of four-month age were divided in the following experimental groups: Baseline (sacrificed at the beginning of the experiment); Intact; Ovx; Ovx + 20, 40, 60, 80 and 100 ppm of NaF, delivered in drinking water. These groups were sacrificed after different periods of time (4, 6, and 8 months). Biometrical, biomechanical, physical and biochemical parameters of the vertebral body (L5) of the animals were measured, together with the fluoride content of the right tibia. Fluoride content present in the right tibia showed a good numerical correlation with the administered dosage for the three different periods of treatment. The ovariectomy promoted a higher body weight gain, and also, a decrease in the values of the biomechanical, physical and biochemical parameters of the vertebral body of the animals for all the periods analysed. Treatment using fluoride at high dosage levels (60, 80, and 100 ppm of NaF) resulted in an increase of bone mass, for the periods of 4 and 8 month of treatment. However, this increase did not induce a higher mechanical resistance of the bones, although at low dosages, 20 and 40 ppm, administered during a 6-month period, a protective effect on the bone tissue was observed, thus preventing a decrease in the biomechanical parameters induced by ovariectomy. As a conclusion, this study showed that low dosages of fluoride can act as a promising therapeutic agent for the prevention of human postmenopausal osteoporosis.